The role of optical coherence tomography and other intravascular imaging modalities in cardiac allograft vasculopathy - Dyrbuś, Maciej; Gąsior, Mariusz; Szyguła-Jurkiewicz, Bożena; Przybyłowski, Piotr (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2020)
Orthotopic heart transplantation (OHT) is the standard-of-care for end-stage heart disease. Although a significant improvement in the prognosis of patients after OHT has been observed in recent years, their overall mortality remains relatively high, with a median survival of approximately 10 years after transplantation. One of the primary causes of death in patients after OHT is cardiac allograft vasculopathy (CAV), the condition developing specifically in the coronary vasculature after OHT, the pathophysiology of which is still inadequately known. It is estimated that CAV development and progression is responsible for approximately 30% of deaths within five years post-OHT. According to the International Society for Heart and Lung Transplantation (ISHLT) Nomenclature for CAV, its presence should be assessed primarily by the coronary angiography performed routinely after OHT, mostly due to its wide availability, reproducibility, and low complication rate. However, the analysis of CAV in coronary angiography has limitations, mostly concerning its – sometimes inadequate – sensitivity and specificity. Hence, there is a growing need for the introduction of more accurate methods of CAV assessment, such as intravascular imaging, which through a thorough evaluation of the arterial wall structure and thickness allows the drawbacks of routine angiography to be minimised. The aim of the article was to critically summarise the current findings derived from the analysis of CAV by optical coherence tomography, the other intravascular imaging modalities, such as intravascular ultrasound (IVUS) and IVUS-derived virtual histology, along with physiological assessment with the use of the fractional flow reserve.